2016
DOI: 10.1021/acsami.6b07599
|View full text |Cite
|
Sign up to set email alerts
|

Ga-Promoted Photocatalytic H2 Production over Pt/ZnO Nanostructures

Abstract: Photocatalytic H2 generation is investigated over a series of Ga-modified ZnO photocatalysts that were prepared by hydrothermal methods. It is found that the structural, textural, and optoelectronic properties remarkably depend on the Ga content. The photocatalytic activity is higher in samples with Ga content equal to or lower than 5.4 wt %, which are constituted by Zn1-xGaxO phases. Structural, textural, and optoelectronic characterization, combined with theoretical calculations, reveals the effect of Ga in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Using ethanol as sacrificial agent, Tijare and co-workers reported a relatively similar hydrogen evolution rate (even if the usual difficulties to quantitatively compare different works must be considered) that could be further boosted by using platinum as co-catalyst [167]. However, in this case the improvement caused by platinum was considerably low if compared to its effect on other semiconducting catalysts [157]. Indeed, Iervolino and co-workers studied LaFeO3 as a promising noble-metal-free hydrogen evolution photocatalyst [168].…”
Section: Single-phase Ferrite Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using ethanol as sacrificial agent, Tijare and co-workers reported a relatively similar hydrogen evolution rate (even if the usual difficulties to quantitatively compare different works must be considered) that could be further boosted by using platinum as co-catalyst [167]. However, in this case the improvement caused by platinum was considerably low if compared to its effect on other semiconducting catalysts [157]. Indeed, Iervolino and co-workers studied LaFeO3 as a promising noble-metal-free hydrogen evolution photocatalyst [168].…”
Section: Single-phase Ferrite Photocatalystsmentioning
confidence: 99%
“…In photocatalytic hydrogen evolution reactions, the presence of a co-catalyst, most generally a noble metal, improves the hydrogen yield by boosting charge separation and acting as catalytic sites for H-H bond formation [157]. In addition, in the case of some metals with appropriate particle size, the localized surface plasmon resonance effect may enhance light absorption in the visible range [114].…”
Section: Single-phase Ferrite Photocatalystsmentioning
confidence: 99%
“…Other than transition metals, post‐transition metal is rarely paid close attention. Ga has been widely used in the fields of optical materials to achieve regional enrichment of photogenerated electrons [6b, 12] . The main reason for long afterglow luminescence is due to the excited electron can be stored at the empty p orbital of Ga sites.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of photocatalysis, Víctor A. de la Peña O'Shea et al. found that Ga doping on Pt/ZnO can maximize the photocatalytic hydrogen evolution efficiency [6b] . Cabot's group [12] reported that a certain amount of photogenerated electrons can be injected at the Ga site in the Ga doping CuInS 2 , which improves the separation efficiency of photogenerated carriers and maximizes the photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…These organic compounds can be degraded photocatalytically under UV light or electrocatalycally by applying a current density at the anode material (Baddouh et al, ; Garcia‐Segura & Brillas, ; Holkar, Jadhav, Pinjari, Mahamuni, & Pandit, ; Martínez‐Huitle & Brillas, ). Different semiconductor photocatalysts have been explored, including metal oxides (Núñez et al, ; Yu et al, ), phosphates (Chennah et al, , ; Naciri et al, ; Zeng et al, ), etc. However, most of these materials still suffer from the rapid recombination of photo‐induced carriers, and the poor light utilization, which limits their photocatalytic efficiency and thus their practical application.…”
Section: Introductionmentioning
confidence: 99%